Iranica II (Nos. 9-31) - Szemerényi, Oswald
includes Hūža ‘Elam’; Hvārazmiš; OP a-ra-ša-na-i-ša, van- ‘throw’, anušiya, azdā, *trs- ‘fear’, kamna-, patiyāvahyaiy, duwitāpara(a)nam čašma, rādiy; OIran. madu.